2019
DOI: 10.1111/imj.14209
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol loading before total parathyroidectomy with autotransplant in patients with end‐stage kidney disease: does it prevent postoperative hypocalcaemia?

Abstract: Background Hungry bone syndrome (HBS) is one of the most serious complications following parathyroidectomy for severe hyperparathyroidism. There is a lack of literature informing the treatment and risk factors for this condition and the ideal pre‐operative strategy for prevention. Aims The primary aims were to examine the incidence of HBS with pre‐operative calcitriol loading for 10 days and to determine the risk factors for HBS. The secondary aims were to determine the rate of intravenous calcium replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Alternatively, an approach based on a 10-day calcitriol loading protocol before PTx in individuals with RHPT might decrease the rate of HBS, yet, it is not unanimously agreed upon. One study on 45 participants who received this mentioned type of intervention developed HBS (28.3% of them) following total PTx with auto-transplantation; HBS positively correlated with pre-operatory PTH levels, and with duration of dialysis before surgery [127]. In addition to calcium and calcitriol supplementation, the use of dialysis represents another key factor to the outcome of HBS in patients with chronic kidney disease, as similarly seen in influencing other endocrine complications of the renal condition [133][134][135].…”
Section: Study Design Studied Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, an approach based on a 10-day calcitriol loading protocol before PTx in individuals with RHPT might decrease the rate of HBS, yet, it is not unanimously agreed upon. One study on 45 participants who received this mentioned type of intervention developed HBS (28.3% of them) following total PTx with auto-transplantation; HBS positively correlated with pre-operatory PTH levels, and with duration of dialysis before surgery [127]. In addition to calcium and calcitriol supplementation, the use of dialysis represents another key factor to the outcome of HBS in patients with chronic kidney disease, as similarly seen in influencing other endocrine complications of the renal condition [133][134][135].…”
Section: Study Design Studied Populationmentioning
confidence: 99%
“…An amount of 23 studies were retrospective and 4 were of prospective, prospective-retrospective type, respectively, longitudinal and a national database cohort. Considering the number of enrolled participants per study, 12 studies included less than 100 participants per study, as follows: 19 (n = 2), 35, 37 (n = 2), 41, 45, 53, 62, 77, 79, 84; 9 studies enrolled between 100 and 200 individuals per study (of 108, 115, 120, 130, 131, 141, 148, 167, and 196), 3 studies had between 200 and 300 patients per study (specifically, 252, 260, and 297) while 3 larger studies had more than 700 patients per study (N = 796, 1846, and 7171), regardless the study design, a total of 12,468 patients with RHPT [1,4,17,30,40,84,85,[104][105][106][107][108][109][110]112,116,117,[123][124][125][126][127][128][129][130][131][132] (Table 5).…”
Section: Post-operatory Findings In Rhpt: Focus On Hbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, there is little knowledge on how we can effectively reduce or prevent this complication. The use of pre-operative loading calcium and/or calcitriol supplement has controversial results [11][12][13][14][15]. On the other hand, studies have shown that poorly controlled severe RHPT (manifested as high pre-operative PTH levels) led to more severe and more frequent hypocalcemia [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%